Fermi level pinning at CdS/Cu(In,Ga)(Se,S) 2 interfaces: effect of chalcopyrite alloy composition - Turcu, M.; Rau, U. (The Journal of physics and chemistry of solids, 2003)
We introduce a quantitative model for the band diagram of ZnO/CdS/Cu(In,Ga)(Se,S) 2 heterostructures and for carrier recombination at the CdS/chalcopyrite interface. We derive analytical expressions for the open circuit voltage and the Fermi energy position at the active interface. The open circuit voltage under interface recombination is almost independent from the band gap energy of the chalcopyrite when the valence band edge of the absorber remains at the same energy position. The analytical calculations are in relatively good agreement with numerical simulations. Experimental current–voltage analysis indicates that devices prepared from Cu-poor Cu(In,Ga)(Se,S) 2 chalcopyrites are dominated by recombination in the bulk of the absorber while interface recombination prevails if the absorbers are prepared under Cu-excess. In the latter case, the experimentally determined interface barriers reveal that the interface Fermi energy position shifts upward on the energy scale upon increasing the Ga content into the absorber and remains at a relatively low energy value under S/Se alloying.